Children and youth with autism spectrum disorder (ASD) : recent advances and innovations in assessment, education, and intervention - Luiselli, James K. (Oxford University Press, 2014)
Autism spectrum disorder (ASD) is a relatively new diagnostic label which reflects the variability and differentiation of symptomatology among children and youth commonly described as having autistic disorder, high-functioning autism (HFA), and Asperger's syndrome. Current best practices have emerged from decades of evidence-based research, research-to-practice translation of empirically supported procedures, and consensus-driven recommendations from multiple disciplines. As a result, practitioners have many educational and intervention choices for children and youth with ASD--what is critical.